PENDAMPINGAN PEMANFAATAN WHATSAPP BISNIS DAN INSTAGRAM BISNIS SEBAGAI MEDIA PEMASARAN DIGITAL PADA UMKM BERKAH DESA JEPITU - Rahmawati, Nur; Mulyaningsih, Sri; Vienastra, Septian; Suhartono, Suhartono; Hidayati, Fika; Emilliana Natalia Trisakti Susanti, Maria; Arif Wardana, Muhammad (Universitas PGRI Yogyakarta, 2024)
Jepitu Village is located in a karst hill area covering an area of ​​1,625.1960 km². Most of the population works as dryland farmers, gardeners, livestock breeders, and fishermen. Despite having abundant natural resources, including agricultural and marine products, local small businesses (MSMEs) face challenges in marketing their products, most of which have limited reach. To overcome this, the community service team assists in using WhatsApp Business and Instagram Business as digital marketing platforms for MSMEs in Jepitu. This training aims to improve product marketing through digital content creation and social media strategies. WhatsApp and Instagram Business offer features that facilitate customer interaction, such as automatic replies and product catalogs. This mentoring program has five stages: socialization, training, technology application, mentoring, and sustainability. The results show a significant increase in participants' understanding and use of digital marketing media, expanding marketing reach and increasing sales. Keywords: MSMEs, digital marketing, WhatsApp Business, Instagram Business